Students’ Group Work Learning Performance in English Offline Learning - Mukhlisah Syahrul; Maemuna Muhayyang; Ryan Rayhana Sofyan (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
This study aims to discover students' group work learning performance in offline learning. This research is a qualitative study using a descriptive qualitative method in collecting data which aims to explore the students' performance in group work during offline learning. The participants of this study were the students in grade XI MIPA 2 and one English teacher of SMAN 1 Pangkep. The instrument used in this study was an observation, with an observation checklist as the tool. The research found that based on the observation tool, the observation checklist, most of the students fulfilled the criteria, making their group work perform properly. There were six items with which most of the groups met with them. However, several items were not in group six’s performance. Based on the findings, it can be concluded that the students had an adequate performance in group work based on the criteria of the observation. The students of SMAN 1 Pangkep are enthusiastic when working together to complete their tasks. They shared their roles and responsibilities with group members and encouraged each other to improve their communication skills and confidence.